Pemanfaatan Media Dakwah Melalui Akun Tiktok @Syam_Elmarusy Dalam Menyampaikan Dakwah Islam - Intan Khoiriyah; Hadi Ismanto (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah bekerjasama dengan LP2M Institut Pesantren Sunan Drajat Lamongan, 2022)
This study aims to break the creativity of young da'i who create interesting content so that mad'u can easily understand the da'wah message conveyed. This research use desciptive qualitative approach. It is hoped that this research can make knowledge for a new generation of young da'i in making da'wah content creatively and informatively in the era of today's challenges.The impact of the use of this research are: 1.) Being able to access knowledge of religious knowledge easily. 2). Lots of new education and broad knowledge gained. 3.) Able to provide income or profit value that has been successfully Obtained for creative preachers such as Ustadz Syamsuddin Nur.